NEW DATA ON THE GOLD-ANTIGORITE ASSOCIATION OF THE URALS - Murzin V.V.; Shanina S.N.; Varlamov D.A. (My University, 2007)
Many placers of the Urals spatially associated with massifs of serpentinized ultramafic rocks contain gold–magnetite associations. The bedrock analogs of this association are rare, small, and interpreted as derivatives of granitoid magmatism. Gold–magnetite occurrences in the Kagan alpinotype ultramafic massif in the South Urals, for example, served as a basis for distinguishing the Au-productive serpentinite (antigorite) metasomatic association. In addition to the spatial association of gold mineralization with antigorite serpentinites, the existence of this association is substantiated by the fact of significant redistribution and mobilization of Au during the development of antigorite, which allowed us to suggest that gold mineralization in the antigorite serpentinites was formed during crustal regional or local metamorphism of the ultramafic massifs under crustal conditions. The present study of gold–magnetite ores and altered rocks of the Kagan massif revealed mineralogical and isotopic–geochemical evidence for the metamorphic origin of mineralization. In this model, fluid and ore components (Fe, Cu, and Au) were mobilized from ultrabasic rocks.